Marketing Communication on TikTok: Mapping the Intellectual Landscape Through a Systematic Literature Review - Bisma Arraafi; Johantan Alfando W; Dony Kristian; Ziya Ibrizah (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
This study systematically reviews the intellectual development of TikTok marketing communication research by synthesizing 52 Scopus-indexed journal articles published between 2020 and May 2025. TikTok has evolved from a short-form entertainment platform into an algorithmic, creator-driven, and transactional communication ecosystem; however, existing studies remain fragmented across themes, theories, methods, and research contexts. Guided by the PRISMA 2020 framework, this review applied a structured search strategy, explicit eligibility criteria, and thematic synthesis to identify publication trends, theoretical foundations, methodological patterns, dominant research themes, and future research directions. The findings show that scholarly attention increased sharply from 2020 to 2022, with research concentrated in Asian contexts and published mainly in journals related to retailing, consumer behavior, information systems, and business studies. The literature is dominated by consumer-response theories, particularly Uses and Gratification Theory, Stimulus–Organism–Response, and the Technology Acceptance Model, while strategic communication perspectives such as Integrated Marketing Communication remain underdeveloped. Methodologically, most studies rely on quantitative survey designs, especially SEM and PLS-SEM, with limited use of longitudinal, experimental, mixed-methods, and computational approaches. The thematic synthesis identifies seven major domains: content strategy, influencer and creator marketing, consumer engagement, algorithmic visibility, electronic word-of-mouth, brand communication, and social commerce. By integrating these fragmented findings, this review advances TikTok marketing communication scholarship beyond isolated consumer-response models and offers a conceptual basis for future research on algorithmic visibility, creator-led persuasion, ethical platform governance, and social commerce integration.